Greening our future: cultural policy and the ecological imperative - Vânia Rodrigues (European Journal of Cultural Management and Policy)
What is it exactly about the quest to “green” the performing arts that so fundamentally challenges the sector’s modi operandi? A sense of urgency around climate change and ecological degradation is informing profound changes in the way the arts field sees itself and slowly inducing a discussion on the sustainability of its working practices. However, despite the undeniable planetary emergency, the lumping together of environmental issues and cultural policy and management frameworks remains complex and controversial, especially if considered from the perspective of the European semi-peripheries. By exploring the preliminary results of a nation-wide inquiry among 140 performing arts regularly funded organisations based in Portugal, this paper discusses the implications of the overarching challenge of environmental sustainability for cultural policymaking and arts management, seeking to contribute to a more nuanced and context-sensitive understanding of the “green transition.”